Dynamics of Inter-Meeting Time in Human Contact Networks - Yoneki, E.; Greenfield, D.; Crowcroft, J. (2009 International Conference on Advances in Social Network Analysis and Mining : 20-22 July 2009, 2009)
We envision new communication paradigms, using physical dynamic interconnectedness among people. Delay Tolerant Networks (DTNs) are a new communication paradigm to support such network environments, and our focus is a type of DTN that provides intermittent communication for humans carrying mobile devices: the Pocket Switched Network (PSN). Information propagation in PSNs is highly influenced by human connectivity networks, i.e. social networks. In our previous work, we have exploited constructing weighted networks using characteristics of pair connections such as the duration of contact time and frequency of contacts from time series of human connectivity network traces. The approach we took is based on empirical and heuristic and the focus is finding a single aggregated logical network structure. The physical network topology in the real world is time dependent and it is a complex task to describe its dynamics. This paper aims to identify dynamics of meeting groups in human connectivity traces, where meeting groups are expected to be a group interacting among the nodes in physical space. Thus, we define dasiameeting grouppsila differently from dasiacommunitypsila. We exploit statistical approach that provides quantitative attributes to uncover meeting groups. We identify the power law behavior of meetings that is important for supporting to understanding dynamics of information flow between meeting groups and building group oriented communication protocol.